2020
DOI: 10.1038/s41598-020-69410-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of native plant growth promoting rhizobacteria and their anti-oomycete potential against Phytophthora capsici affecting chilli pepper (Capsicum annum L.)

Abstract: Phytophthora capsici is a notorious fungus which infects many crop plants at their early and late growth stages. in the present study, twelve P. capsici isolates were morphologically characterized, and based on pathogenicity assays; two highly virulent isolates causing post-emergence damping-off on locally cultivated chilli pepper were screened. two P. capsici isolates, HydPak1 (MF322868) and HydPk2 (MF322869) were identified based on internal transcribed spacer (ITS) sequence homology. Plant growth promoting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 81 publications
0
35
0
Order By: Relevance
“…Concerning the isolated bacteria, 11.67 % were from roots, 63.33 % from the rhizosphere, 8.3 % from leaves and 11 % from stem. Previous studies also report on various biocontrol potential of bacteria belonging to the genera Pseudomonas and Bacillus 36 , Bacillus subtlis and Actinomycetes 37 being the most common bacterial groups showing in pepper plants. Bacterial colonization appeared to be abundant in the rhizosphere pepper plants, which may be a re ection of a primary site for bacterial nutrients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Concerning the isolated bacteria, 11.67 % were from roots, 63.33 % from the rhizosphere, 8.3 % from leaves and 11 % from stem. Previous studies also report on various biocontrol potential of bacteria belonging to the genera Pseudomonas and Bacillus 36 , Bacillus subtlis and Actinomycetes 37 being the most common bacterial groups showing in pepper plants. Bacterial colonization appeared to be abundant in the rhizosphere pepper plants, which may be a re ection of a primary site for bacterial nutrients.…”
Section: Discussionmentioning
confidence: 98%
“…V.H.18, AULE41-Pseudomonas uorescence and AAULE51-un identi ed showed > 52.5% mycelial growth inhibition of Phytophthora capsici. 36 studied the antagonistic effects of bacterial strains and found that, out of fteen tested rhizospheric bacteria, ve bacterial strains showed > 70% of antagonistic potential against P.capsici. In other study from 48 threeisolates were found to control P.capsici both in vivo and in vitro 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Auxinitriggersiainumber of cellularifunction rangingifrom differentiationiof vascular tissues,iinitiation ofilateral and adventitiousiroots, stimulation oficell division, elongationiof stems andiroots, and orientationiof root and shoot growth in response to light and gravity [21,22]. Six rhizobacteria strains, were produce IAA that able to increased shoot, stem and root length of chilli pepper [23].…”
Section: Vegetative Plant Growthmentioning
confidence: 99%
“…1aminocyclopropane-1-carboxylate deaminase activity, nitrogen fixation, phosphorus solubilization, potassium solubilization, indolacetic acid production, siderophore production, production of hydrolytic enzymes (e.g., α-amylase, cellulase, chitinase, pectinase, protease), antibiotic production, hydrogen cyanide production, ammonia production, fungal antagonistic activity, etc. (Glick, 2012;Dinesh et al, 2015;Burges et al, 2017;Hyder et al, 2020). It must be emphasized that all these lab-tested traits only represent potentiality but not reality, since the inoculated microbial strains must also show ecological competence and functional performance in the specific soilplant system under consideration (actually, in many cases, they do not survive or grow properly, or do not produce the required phenotype, once they have been inoculated) (Nelson, 2004;Backer et al, 2018).…”
Section: Symbiosis Approachesmentioning
confidence: 99%